Identifikasi Tiga Risiko Tertinggi terhadap Efektivitas K3 dengan Metode HIRADC pada Proyek Konstruksi Gedung Fakultas Ilmu Budaya Universitas Airlangga - Darmawan, Rifky; Witjaksana, Budi (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to identify and analyze the effect of OHS implementation on project costs in the construction of the Faculty of Humanities Building at Universitas Airlangga Campus B Surabaya. The method used is Hazard Identification, Risk Assessment and Determining Control (HIRADC) to identify potential hazards and levels of work risk. Data were obtained through questionnaires and project documents related to the implementation of OHS procedures and project costs. The results show that the three highest identified risks are the risk of falling from height with a risk value of 12 (high category), the risk of being struck by materials with a risk value of 10 (high category), and the risk of electric shock with a risk value of 9 (medium category). After the implementation of risk control measures such as the use of personal protective equipment, installation of safety devices, and increased supervision, the risk level decreased by 33% from the initial condition. This indicates that the implementation of OHS is not only effective in improving work safety, but also contributes positively to risk control in construction projects.